Analisis Pembelajaran Blended Learning Dalam Meningkatkan Hasil Belajar Siswa Kelas I Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis Indramayu - Sulastri, Imas; Satria, Alfi (JUPE : Jurnal Pendidikan Mandala, 2023)
The covid-19 pandemic has forced the entire education sector in Indonesia to adapt to a new learning system, namely online learning. However, the implementation of online learning is still not effectively implemented in rural areas which in the end students' interest in learning has decreased this can be seen from student learning outcomes. One of the elementary schools in the blood of the researchers also experienced the same difficulties, so the researchers conducted a study that aimed to analyze blended learning which became an alternative method of the learning process at MI Muhammadiyah Sukajati Haurgeulis Indramayu. This study used descriptive qualitative method. Collecting data through observation, interviews with teachers and students, and documentation. By using random sampling technique. From this study, it was found that the learning outcomes of the first grade students of MI Muhammadiyah Sukajati Haurgeulis Indramayu in the cognitive domain had increased. Blended learning at MI Muhammadiyah Sukajati Haurgeulis Indramayu uses a shift system by dividing students into several groups.